Cellular Pathology of Pelizaeus-Merzbacher Disease Involving Chaperones Associated with Endoplasmic Reticulum Stress - Inoue, Ken (Frontiers in Molecular Biosciences, 2017)
Disease-causing mutations in genes encoding membrane proteins may lead to the production of aberrant polypeptides that accumulate in the endoplasmic reticulum (ER). These mutant proteins have detrimental conformational changes or misfolding events, which result in the triggering of the unfolded protein response (UPR). UPR is a cellular pathway that reduces ER stress by generally inhibiting translation, increasing ER chaperones levels, or inducing cell apoptosis in severe ER stress. This process has been implicated in the cellular pathology of many neurological disorders, including Pelizaeus-Merzbacher disease (PMD). PMD is a rare pediatric disorder characterized by the failure in the myelination process of the central nervous system (CNS). PMD is caused by mutations in the PLP1 gene, which encodes a major myelin membrane protein. Severe clinical PMD phenotypes appear to be the result of cell toxicity, due to the accumulation of PLP1 mutant proteins and not due to the lack of functional PLP1. Therefore, it is important to clarify the pathological mechanisms by which the PLP1 mutants negatively impact the myelin-generating cells, called oligodendrocytes, to overcome this devastating disease. This review discusses how PLP1 mutant proteins change protein homeostasis in the ER of oligodendrocytes, especially focusing on the reaction of ER chaperones against the accumulation of PLP1 mutant proteins that cause PMD.